Integral of cos^4xsin^5xdx dx
The solution
Detail solution
-
Rewrite the integrand:
cos4(x)sin5(x)1=(1−cos2(x))2sin(x)cos4(x)
-
There are multiple ways to do this integral.
Method #1
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute du:
∫(−u8+2u6−u4)du
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u8)du=−∫u8du
-
The integral of un is n+1un+1 when n=−1:
∫u8du=9u9
So, the result is: −9u9
-
The integral of a constant times a function is the constant times the integral of the function:
∫2u6du=2∫u6du
-
The integral of un is n+1un+1 when n=−1:
∫u6du=7u7
So, the result is: 72u7
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u4)du=−∫u4du
-
The integral of un is n+1un+1 when n=−1:
∫u4du=5u5
So, the result is: −5u5
The result is: −9u9+72u7−5u5
Now substitute u back in:
−9cos9(x)+72cos7(x)−5cos5(x)
Method #2
-
Rewrite the integrand:
(1−cos2(x))2sin(x)cos4(x)=sin(x)cos8(x)−2sin(x)cos6(x)+sin(x)cos4(x)
-
Integrate term-by-term:
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute −du:
∫u8du
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u8)du=−∫u8du
-
The integral of un is n+1un+1 when n=−1:
∫u8du=9u9
So, the result is: −9u9
Now substitute u back in:
−9cos9(x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−2sin(x)cos6(x))dx=−2∫sin(x)cos6(x)dx
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute −du:
∫u6du
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u6)du=−∫u6du
-
The integral of un is n+1un+1 when n=−1:
∫u6du=7u7
So, the result is: −7u7
Now substitute u back in:
−7cos7(x)
So, the result is: 72cos7(x)
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute −du:
∫u4du
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u4)du=−∫u4du
-
The integral of un is n+1un+1 when n=−1:
∫u4du=5u5
So, the result is: −5u5
Now substitute u back in:
−5cos5(x)
The result is: −9cos9(x)+72cos7(x)−5cos5(x)
Method #3
-
Rewrite the integrand:
(1−cos2(x))2sin(x)cos4(x)=sin(x)cos8(x)−2sin(x)cos6(x)+sin(x)cos4(x)
-
Integrate term-by-term:
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute −du:
∫u8du
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u8)du=−∫u8du
-
The integral of un is n+1un+1 when n=−1:
∫u8du=9u9
So, the result is: −9u9
Now substitute u back in:
−9cos9(x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−2sin(x)cos6(x))dx=−2∫sin(x)cos6(x)dx
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute −du:
∫u6du
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u6)du=−∫u6du
-
The integral of un is n+1un+1 when n=−1:
∫u6du=7u7
So, the result is: −7u7
Now substitute u back in:
−7cos7(x)
So, the result is: 72cos7(x)
-
Let u=cos(x).
Then let du=−sin(x)dx and substitute −du:
∫u4du
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u4)du=−∫u4du
-
The integral of un is n+1un+1 when n=−1:
∫u4du=5u5
So, the result is: −5u5
Now substitute u back in:
−5cos5(x)
The result is: −9cos9(x)+72cos7(x)−5cos5(x)
-
Now simplify:
−315(35sin4(x)+20sin2(x)+8)cos5(x)
-
Add the constant of integration:
−315(35sin4(x)+20sin2(x)+8)cos5(x)+constant
The answer is:
−315(35sin4(x)+20sin2(x)+8)cos5(x)+constant
The answer (Indefinite)
[src]
/
| 5 9 7
| 4 5 cos (x) cos (x) 2*cos (x)
| cos (x)*sin (x)*1 dx = C - ------- - ------- + ---------
| 5 9 7
/
∫cos4(x)sin5(x)1dx=C−9cos9(x)+72cos7(x)−5cos5(x)
The graph
5 9 7
8 cos (1) cos (1) 2*cos (1)
--- - ------- - ------- + ---------
315 5 9 7
−5cos5(1)−9cos9(1)+72cos7(1)+3158
=
5 9 7
8 cos (1) cos (1) 2*cos (1)
--- - ------- - ------- + ---------
315 5 9 7
−5cos5(1)−9cos9(1)+72cos7(1)+3158
Use the examples entering the upper and lower limits of integration.